Smart healthcare applications and services developments and practices - Rocker, Carsten, 1975-; Ziefle, Martina, 1962-; IGI eBooks; IGI Global (Hershey, Pa. : IGI Global (701 E. Chocolate Avenue, Hershey, Pennsylvania, 17033, USA), 2011)
Provides an in-depth introduction into medical, social, psychological, and technical aspects of smart healthcare applications as well as their consequences for the design, use and acceptance of future systems.
11. Interactivating rehabilitation through active multimodal feedback and guidance / Bert Bongers, Stuart Smith -- 12. Mapping input technology to ability / Ainara Garzo, Stefan P. Carmien, Xabier Madina -- 13. Restoring balance : replacing the vestibular sense with wearable vibrotactile feedback / Maria Jlia S. Benini ... et al. -- 14. A home-based system to support delivery of health and social care / Kenneth J. Turner.
Includes bibliographical references.
Also available in print.
Mode of access: World Wide Web.
Description based on title screen (IGI Global, viewed Feb. 12, 2011).
Keywords: Home care services; Medical informatics; Medical telematics; Medical technology; Telemedicine -- instrumentation; Independent Living; Monitoring, Ambulatory -- instrumentation; Patient Compliance; Adaptive and tangible user interfaces for e-health systems; Ambient assisted living environments; Handheld devices and mobile computing in e-health systems; Human aspects of future and emerging healthcare technologies; Model-based design of e-health systems; Privacy, security, and trust in e-health applications; Social and societal implications of e-health applications; Software infrastructures and architectures for implementing e-health applications; Technologies and devices for smart healthcare systems; Usability of healthcare information systems; Electronic books